Alpha-Klotho is a novel predictor of treatment responsiveness in patients with heart failure - Manabu Taneike (Nature Portfolio, 2021)
Abstract Heart failure is a major cause of death with an increasing population of elderly individuals. Several studies have demonstrated the involvement of soluble alpha-Klotho (sαKl) in various diseases. However, the correlation between sαKl and heart failure remains to be understood. The aim of this study is to investigate the levels and role of sαKl in patients with heart failure. Twenty-eight consecutive patients with acute heart failure (19 male, 9 female), admitted to the Osaka University Hospital from 2010 to 2018, were enrolled in this study. Mean NYHA score, left ventricular ejection fraction and BNP were 3.3, 17.0% and 588 pg/mL, respectively. SαKl significantly increased in heart failure patients. SαKl on admission were significantly higher in patients with heart failure who showed improvement after intensive treatment than that in patients who did not show improvement after the treatment. SαKl levels decreased significantly in patients who showed improvement. Interestingly, sαKl levels increased in male patients with heart failure, but not in female patients. Our data suggest that soluble αKl may be a novel biomarker for the responsiveness against treatment in patients with heart failure with reduced ejection fraction. Our findings may help developing a personalized therapy for different patients with heart failure.